Improved Glycemic Control and Risk of ESRD in Patients with Type 1 Diabetes and Proteinuria - Skupien, Jan (J Am Soc Nephrol, 2014)
Most patients with type 1 diabetes (T1D) and proteinuria have poor glycemic control and a high risk of ESRD. We investigated whether long-term improvement of glycemic control reduces risk of ESRD in a prospective 7- to 15-year follow-up observation of 349 patients with CKD stages 1–3 enrolled in the Joslin Proteinuria Cohort of adults with T1D. All patients developed proteinuria between 1990 and 2004 and were followed until 2011 to ascertain onset of ESRD and deaths unrelated to ESRD. Furthermore, we analyzed data from 279 patients with ≥3 years of clinic follow-up available to assess the level of glycemic control after enrollment. Average HbA(1c) during the 5 years before study enrollment (prebaseline) was compared with HbA(1c) (postbaseline) averaged during the first half of follow-up (median, 5.1 years). Median prebaseline HbA(1c) was 9.3%, decreasing to 8.7% postbaseline. Cumulative risk of ESRD after 15 years was significantly lower for patients whose HbA(1c) decreased than for those whose HbA(1c) increased or remained poor (29% versus 42%; P<0.001). The difference between these groups was not visible at 5 years of follow-up but became visible at 10 and 15 years of follow-up. In multivariate Cox regression analysis of ESRD risk, the hazard ratio corresponding to a 1–percentage point improvement in postbaseline HbA(1c) was 0.76 (95% confidence interval, 0.63 to 0.91; P=0.003). In conclusion, results of this study suggest that long-term sustained improvement in HbA(1c) decelerates eGFR loss and delays the onset of ESRD in patients with T1D and proteinuria.